Nilai ketebalan kortikal mandibula pada anak dan remaja terinfeksi HIV - Fadhlil Ulum Abdul Rahman; Alongsyah Zulkarnaen Ramadhan; Farina Pramanik; Ria Noerianingsih Firman (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The aim of this study was to obtain the value of mandibular cortical thickness in HIV-infected children and adolescents based on panoramic radiographs. Material and Methods: This descriptive and cross-sectional study was carried out on 43 panoramic radiographs of HIV-infected children and adolescents. The value of mandibular cortical thickness were measured by three indices regarded as mental index (MI), gonial index (GI), and antegonial index (AGI) using a digital calipers directly on the panoramic radiographs which had been taken previously. Results: Among 43 panoramic radiographs, 18 (41,86%) were boys and 25 (58,14%) were girls. Based on age range, there are 30 samples (69,77%) were categorized as children with age range 5-11 years and 13 samples (30,23%) were categorized as adolescents with age range 12-16 years. The lower value of mandibular cortical thickness based on MI, AGI, and AGI was seen in girls compared to boys. The adolescents have a higher value of mandibular cortical thickness compared with the children. Conclusion: There are different values of mandibular cortical thickness in HIV-infected children and adolescents based on sex and age.